Design and fabrication of millifluidic devices for maintenance of tissue cultures under perfusion - Buthelezi, Khanyisile Thando Fatima (Rhodes University, Faculty of Science, Biotechnology Innovation Centre)
Restricted access. Expected release in 2026.
Keywords: Uncatalogued